Envelhecer no campo ou cidade: a escolha de aposentados rurais na comunidade do Cerro do Ouro, Santo Antônio das Missões - RS - Birck, Vitor (2022)
This paper addresses the aging process in rural areas, and in this context discusses the migration of elderly people to urban spaces after retirement. The objective of the research is to understand the perception of the elderly in the Cerro do Ouro Community, Santo Antônio das Missões-RS in relation to the choice of place of residence after retirement, that is, about staying in the countryside or migrating to the city. The methodological approach applied was the qualitative interview with quantitative aspects, with semi-structured questions, conversations and observations. The sample universe comprised 71 elderly people living in the Missões region in the State of Rio Grande do Sul, 46 of whom live in rural areas and 25 elderly people who migrated to the urban area. The questions dealt with issues related to socioeconomic and land tenure aspects, life habits, health, choices, difficulties, etc. Data analysis was descriptive and exploratory. The results show that among the main reasons for the departure of the elderly are health, income and family, factors that are affected by the provision of public services and for those who stay the justification is supported by calm, safety, work and nature. Therefore, the migration of the elderly in the current context is linked to certain particularities faced by the family nuclei, in how the public power supports the needs of the elderly and their income, while the permanence is based on maintaining tranquility and peace.